4CPS-218 Evaluation of the impact of incorporating a pharmacist into a hospital emergency department. (23rd March 2022) - Fresan, D; Ortega, I; Lamas, A; Magro, C; Pino, A; Goñi, N; Erdozain, S; Tejada, D; Rodriguez, A; Sarobe Carricas, MT
Abstract : Background and importance: Attending a hospital emergency department (HED) is considered a high-risk situation regarding medicines appropriate reconciliation and medication errors. Thus, patients may well benefit from incorporating a pharmacist into the healthcare team who helps with medication management review. Aim and objectives: This study aimed to analyse the interventions proposed by the pharmacy team to the medical team in our HED setting and to evaluate the positive impact this may have on patients' management. Material and methods: Patients' prescriptions were assessed and pharmacotherapy changes, if needed, were registered in their clinical history. At the end of the work day, we reviewed if proposals had been accepted or rejected. This prospective study was conducted in a tertiary hospital over 1 month. Results: 200 patients (54% males and 46% females) admitted to HED were evaluated by the pharmacy team. Mean age was 75 (31–99) years. 66 interventions were proposed in 54 patients (27%). 55% were accepted and 22% rejected. The remaining 23% could not be appraised as patients had been discharged prior to the medical team evaluation of the suggestions. Drug-related problems found were: 45% related to reconciliation (overdosing, underdosing, posology disparities, absence or no longer taking medicine prescription); 13% overdosing according to renal function or indication; 10% excessive anticholinergic burden that may have contributed to the current clinical problem; 9% underdosing for the indication; 8% lack of indication; 6% lack of prescription of a highly likely needed drug; 4% duplicities; 3% not optimal drug for the indication and 2% allergy-related problems. Proposed actions were: dosing adjustments (50%), prescription (20%), discontinuation (20%), posology modification (7%) and alternative drug selection (3%). Affected drug families were: antibiotics (22%), antidepressants, antipsychotics and anxiolytics (15%), antithrombotics (14%), blood pressure lowering agents (9%), vitamin and electrolytes supplements (9%), antiepileptics (7%), immunosupressors (4%) and others below 3% of incidence (painkillers, statins, antiretrovirals, antiarrhythmics, anti-gouts, thyroid hormones and eye-drops). Conclusion and relevance: Multidisciplinary teams are beneficial to patients' care. Incorporating a pharmacist in a HED reduces the incidence of medication errors and can positively contribute to the management of patients. Medicines reconciliation, dosing and indication checking and pharmacotherapy optimisation are actions in which the pharmacy team is capable of actively contributing for patients' best outcomes. References and/or acknowledgements: Conflict of interest: No conflict of interest